2022
DOI: 10.1111/jcpp.13651
|View full text |Cite
|
Sign up to set email alerts
|

Sleep influences daily suicidal ideation through affective reactivity to interpersonal events among high‐risk adolescents and young adults

Abstract: Background: Identifying proximal risk factors for suicidal ideation that are modifiable and relevant for adolescents and young adults is critical for suicide prevention. This study used an intensive monitoring approach to examine whether objectively-and subjectively-measured sleep characteristics predict next-day suicidal ideation occurrence and intensity through affective reactivity to interpersonal events in young people at high risk for suicide. Methods: Participants included 59 (13-23 years; 76% White; 75%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Although there is no direct evidence that sleep problems influence an individual's self-regulatory behavior or diminish their capacity for self-control during a suicidal crisis, recent EMA research has shown that poor sleep quality and short sleep duration were temporally associated with suicidal ideation (74). Furthermore, an EMA study (75) with high-risk adolescents has found that shorter-than-usual sleep duration predicted the presence and intensity of next-day suicidal ideation via heightened affective reactivity to negative interpersonal events, a finding in line with the DSMS. According to its assumptions, when a person has depleted self-regulatory resources to sleep deprivation they are not able to downregulate negative affect via effective emotion-regulation strategies and that results in affective dysregulation.…”
Section: Sleepmentioning
confidence: 99%
“…Although there is no direct evidence that sleep problems influence an individual's self-regulatory behavior or diminish their capacity for self-control during a suicidal crisis, recent EMA research has shown that poor sleep quality and short sleep duration were temporally associated with suicidal ideation (74). Furthermore, an EMA study (75) with high-risk adolescents has found that shorter-than-usual sleep duration predicted the presence and intensity of next-day suicidal ideation via heightened affective reactivity to negative interpersonal events, a finding in line with the DSMS. According to its assumptions, when a person has depleted self-regulatory resources to sleep deprivation they are not able to downregulate negative affect via effective emotion-regulation strategies and that results in affective dysregulation.…”
Section: Sleepmentioning
confidence: 99%
“…These items will be deployed using links to a web-based form sent via SMS texts or emails, as in the sleep diary implementation. These items will be assessed in the evening and will include ratings of adolescents' mood; experiences of racism, discrimination, and victimization ( 101 ); and affective and behavioral regulation (impulsivity and reactivity to the day's most positive and negative event as in our prior work) ( 102 ).…”
Section: Multiphase Tsc Adaptation and Evaluation Protocolmentioning
confidence: 99%
“…Here, I learnt about Hamilton et al. (2022)'s study that tests the relationship of sleep quality and duration with suicide ideation using exactly this sort of intensive monitoring design.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…As I was writing this commentary, Journal of Child Psychology and Psychiatry's Early View Alert landed in my inbox. Here, I learnt about Hamilton et al (2022)'s study that tests the relationship of sleep quality and duration with suicide ideation using exactly this sort of intensive monitoring design.…”
Section: Directions For Future Researchmentioning
confidence: 99%